The ALMA REBELS Survey: cosmic dust temperature evolution out to z ∼ 7. Issue 3 (3rd February 2022) - Sommovigo, L; Ferrara, A; Pallottini, A; Dayal, P; Bouwens, R J; Smit, R; da Cunha, E; De Looze, I; Bowler, R A A; Hodge, J; Inami, H; Oesch, P; et al.
ABSTRACT: ALMA observations have revealed the presence of dust in the first generations of galaxies in the Universe. However, the dust temperature T d remains mostly unconstrained due to the few available FIR continuum data at redshift z > 5. This introduces large uncertainties in several properties of high-z galaxies, namely their dust masses, infrared luminosities, and obscured fraction of star formation. Using a new method based on simultaneous [C II ] 158-μm line and underlying dust continuum measurements, we derive T d in the continuum and [C II ] detected z ≈ 7 galaxies in the ALMA Large Project REBELS sample. We find 39 < T d < 58 K, and dust masses in the narrow range M d = (0.9−3.6) × 10 7 M⊙ . These results allow us to extend for the first time the reported T d (z ) relation into the Epoch of Reionization. We produce a new physical model that explains the increasing T d (z ) trend with the decrease of gas depletion time, t dep = M g /SFR, induced by the higher cosmological accretion rate at early times; this hypothesis yields T d ∝ (1 + z ) 0.4 . The model also explains the observed T d scatter at a fixed redshift. We find that dust is warmer in obscured sources, as a larger obscuration results in more efficient dust heating. For UV-transparent (obscured) galaxies, T d only depends on the gas column density (metallicity), T_d N_H^1/6 ( T d ∝ Z −1/6 ). REBELS galaxies are on average relatively transparent, with effective gas column densities around N H ≃ (0.03−1) × 10 21 cm −2 . We predict that other high-z galaxies (e.g. MACS0416-Y1, A2744-YD4), with estimated T d ≫ 60 K, are significantly obscured, low-metallicity systems. In fact, T d is higher in metal-poor systems due to their smaller dust content, which for fixed L IR results in warmer temperatures.